Elderly depression: unnoticed public health problem in India- a study on prevalence of depression and its associated factors among people above 60 years in a semi urban area in Chennai - Mohan, Yogesh; Jain, Timsi; Krishna, S.; Rajkumar, A.; Bonigi, Sathvika (International Journal Of Community Medicine And Public Health, 2017)
Background: Worldwide proportion of elderly population is expected to double from current 12% to 22% by 2050. This growth in elderly population inevitably leads to increase in age related diseases such as depression and serious constrains on quality of life among them. As depression frequently manifest with somatic symptoms like tension, headache and heaviness, etc., most of the elderly persons visit non psychiatry outpatient services seeking relief for their symptoms. Methods: A cross sectional study was done in the field practice area of Saveetha Medical College and Hospital. Geriatric depression scale (GDS) short form was used to measure the level of depression in geriatric population. Structured questionnaire was used in order to assess their physical health, socio-demographic data and social support. Elderly mobility scale was used to measure the level of physical dependency. Proportion and chi-square were used for analysis. Results: Prevalence of depression was found to be 76%. Among depressed elderly 47% had mild depression, 28% had moderate depression and 25% were suffering from severe depression. Severity of depression was also found to be significantly more among those who had lost their life partner and those who were physically dependent on others. Conclusions: Prevalence of depression in the elderly was found to be high moreover none of the elderly were diagnosed to be depressed. Steps like screening for depression among elderly should be undertaken to diagnose the cases of depression, they should be treated and also be given proper counseling sessions to reduce their levels of depression.